Poly(I:C)-induced maternal immune activation causes elevated self-grooming in male rat offspring: Involvement of abnormal postpartum static nursing in dam - Lan, Xing-Yu; Gu, You-Yu; Li, Ming-Juan; Song, Tian-Jia; Zhai, Fu-Jun; Zhang, Yong; Zhan, Jiang-Shan; Böckers, Tobias M.; Yue, Xiao-Nan; Wang, Jia-Nan; Yuan, Shuo; Jin, Meng-Ying; et al. (Frontiers in Cell and Developmental Biology, 2023)
Maternal immune activation (MIA) is closely related to the onset of autism-like behaviors in offspring, but the mechanism remains unclear. Maternal behaviors can influence offspring’s development and behaviors, as indicated in both human and animal studies. We hypothesized that abnormal maternal behaviors in MIA dams might be other factors leading to delayed development and abnormal behaviors in offspring. To verify our hypothesis, we analyzed poly(I:C)-induced MIA dam’s postpartum maternal behavior and serum levels of several hormones related to maternal behavior. Pup’s developmental milestones and early social communication were recorded and evaluated in infancy. Other behavioral tests, including three-chamber test, self-grooming test, open field test, novel object recognition test, rotarod test and maximum grip test, were performed in adolescence of pups. Our results showed that MIA dams exhibit abnormal static nursing behavior but normal basic care and dynamic nursing behavior. The serum levels of testosterone and arginine vasopressin in MIA dams were significantly reduced compared with control dams. The developmental milestones, including pinna detachment, incisor eruption and eye opening, were significantly delayed in MIA offspring compared with control offspring, while the weight and early social communication showed no significant differences between the two groups. Behavioral tests performed in adolescence showed that only male MIA offspring display elevated self-grooming behaviors and reduced maximum grip. In conclusion, MIA dams display abnormal postpartum static nursing behavior concomitantly with reduced serum levels of testosterone and arginine vasopressin, possibly involving in the pathogenesis of delayed development and elevated self-grooming in male offspring. These findings hint that improving dam’s postpartum maternal behavior might be a potential regime to counteract delayed development and elevated self-grooming in male MIA offspring.